Three dimensional printing of bone tissue engineering scaffold: Design, structure, and mechanical properties / Mitra Asadi-Eydivand - Mitra Asadi, Eydivand (2016)
Techniques to restore and replace bones in large fractures are still a major clinical need in the field of orthopedic surgery. Thus, tissue engineering is one of the most hopeful approaches for developing engineered alternatives for damaged bones. Scaffolds are important part of bone tissue engineering (BTE). They are three-dimensional (3D) porous structures that are expected to, at least, partially imitate the extracellular matrix (ECM) of natural bone. Due to the natural properties of bone that are similar to calcium-based ceramics, the fabrication of scaffolds with the same properties as patient’s bone and adaptability to fracture defect are still a matter of concern and have remained a challenging area in the BTE field. Since the microarchitecture of a scaffold, like its pore size, and interconnectivity cannot be fully controlled by conventional techniques, recently, the additive manufacturing (AM) techniques have drawn the attention among tissue engineering experts. Other than that, solid freeform fabrication (SFF) is a wellestablished AM technique that can be employed to produce prototypes from complex 3D data sets. Moreover, the ability of inkjet-based 3D printing (3DP) to fabricate biocompatible ceramics has made it one of the most favorable techniques to build BTE scaffolds. Furthermore, calcium sulfates, which exhibit various beneficial characteristics, can be used as a promising biomaterial in BTE and it is a low-cost material for 3DP. Hence, this project had designed and developed the optimal processing parameters based on the design of the experimental approach and evolutionary algorithms to evaluate the ability of commercial 3D printers for making calcium sulfate-based or in other words, commercial-materials-based scaffold prototypes. Besides the simple design to fulfill the BTE requirements and to study the printing parameters, a library of triply periodic minimal surfaces (TPMS) based unit cells was subjected to finite element analysis and computational fluid dynamic (CFD) simulations. Elastic modulus, compressive strength, as well as permeability, were characterized for different volume fractions of TPMS structures to develop structure-property correlations with emphasis on describing the architectural features of optimum models. The major printing parameters examined in this study for the simple design were layer thickness, delayed time of spreading the next layer, and build orientation of the specimens. However, low mechanical performance caused by the brittle character of ceramic materials had been the main weakness of the 3DP calcium sulfate scaffolds. Moreover, the presence of certain organic matters in the starting commercial powder and binder solution caused the products to have high toxicity levels. So, after fabrication, post-processing treatments were employed upon optimal specimens to further improve the physical, the chemical, and the biological behaviors of the printed samples. The first post-processing technique was heat treatment, while the second one was phosphate treatment of 3D-printed specimens to convert the calcium sulfate-based prototypes to calcium phosphate ones solely to improve their properties.